Поняття цивільно-правового договору - Мороз, О. В.; Moroz, O. V.; ORCID: http://orcid.org/0000-0003-4154-1826 (Право і суспільство. - 2023. - № 1. - С. 90-95, 2023)
Досліджено та здійснено аналіз поняття цивільно-правового договору з точок зору правочину, правовідношення та документу. Зазначено, що цивільно-правовий договір потрібно визначати як юридичний акт двох або більше осіб, заснований на їх погоджених діях, виражений у вільному волевиявленні, спрямований на досягнення єдиного правового результату, який полягає у встановленні, зміні і припиненні цивільних прав та обов’язків і зафіксований у встановленій законом формі.

The concept of the Civil law contract is investigated and analysed in terms of deed, legal relationship and an act. It is pointed that the single term “contract” applies to different legal phenomena, namely: an agreement that is a type of deed; legal relationship resulting from the concluded agreement; and a document as a form of existence of a contractual relationship. It was determined that the content of the agreement is in the mutual expression of the will of the parties to the civil law contract. It is pointed out that the civil law contract is considered as a binding agreement enforced by the civil law rules, the participants of which possess subjective rights and obligations. It was determined that there are three points of view in the literature regarding the relationship between the significance of the law and the civil contract. The “will theory” was analyzed, the supporters of which believe that the contract as a voluntary act of the counterparties is the primary source, and the law only supplements or limits their will. The theory of “priority of the law” was studied, the supporters of which believe that a civil law contract is endowed only with a legal effect derived from the law. An analysis of the “empirical theory” was carried out, the supporters of which believe that the will of the parties is deliberately aimed at a certain economic effect; at the same time, the consequences of the contract are imagined as means of its implementation, about which the parties may not have a clear idea. The “subjective” and “objective” theories of the contract are studied. It is indicated that the “subjective” theory defines a contract as an agreement between two or more persons aimed at establishing mutual rights and obligations. The “objective” theory of the contract determines the influence of the state on the process of conclusion and execution of contracts based on the formal equality of the parties to the contract and their freedom of expression. It was determined that a civil law contract should be defined as a legal act of two or more persons, based on their agreed actions, expressed in free will, aimed at achieving one legal result, which consists in establishing, changing and terminating civil rights and obligations and recorded in the form prescribed by law.

Исследован и проведен анализ понятия гражданско-правового договора с точки зрения сделки, правоотношения и документа. Отмечено, что гражданско-правовой договор следует определять как юридический акт двух или более лиц, основанный на их согласованных действиях, выраженный в свободном волеизъявлении, направленный на достижение единого правового результата, заключающийся в установлении, изменении и прекращении гражданских прав и обязанностей и зафиксированный в установленной законом форме.
The Concept of the Civil Law Contract
Мороз, О. В. Поняття цивільно-правового договору / Мороз О. В. // Право і суспільство. - 2023. - № 1. - С. 90-95. - DOI: https://doi.org/10.32842/2078-3736/2023.1.13.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; договір; contract; договор; цивільно-правовий договір; civil law contract; гражданско-правовой договор; погляди вчених; views of scientists; взгляды ученых